Chelate Polymers of Alkaline-Earth Metals with Bis(8-hydroxy-5-quinolyl)-methane - Prakash, Dharam; Kumar Yadav, Ashok (Asian Journal of Chemistry, 2010)
Four chelate polymers of alkaline-earth metals with bis(8-hydroxy- 5-quinolyl)-methane having the general formula [ML´]n where M = Mg, Ca, Sr or Ba and L´ = deprotonated bis(8-hydroxy-5-quinolyl)-methane, have been synthesized and characterized. Their FTIR spectra suggest the coordination of the alkaline-earth metal through oxygen atom of hydroxy group as well as nitrogen atom of quinoline ring.